Co-administration of vitamin D and N-acetylcysteine to modulate immunosenescence in older adults with vitamin D deficiency: a randomized clinical trial - Rastgoo, Samira; Pourvali, Katayoun; Raeissadat, Seyed Ahmad; Eslamian, Ghazaleh; Zand, Hamid (Frontiers in Immunology, 2025)
BackgroundImmunosenescence is an important factor in the impaired immune response in older adults and plays a significant role in the development of biological aging. Targeting immunosenescence could present a novel pharmacological approach to mitigating aging and age-related diseases. We aimed to investigate the effect of N-acetylcysteine (NAC) and vitamin D (Vit-D) on the senescence of peripheral blood mononuclear cells (PBMCs).MethodThis randomized clinical trial was conducted on older adults with Vit-D deficiency. Eligible participants were randomly assigned to one of four groups to receive either (A) 1000 IU of Vit-D daily (D1) (B), 1000 IU of Vit-D plus 600 mg of NAC daily (D1N) (C), 5000 IU of Vit-D daily (D5), or (D) 5000 IU of Vit-D plus 600 mg of NAC daily (D5N) for 8 weeks. Senescence-associated beta-galactosidase (SA-β-gal) staining, expression of senescence-related genes, and serum inflammatory factors were measured at baseline and after 8 weeks.ResultsAfter the intervention, supplementation with D5N and D5 significantly downregulated p16, interleukin-6 (IL-6), and tumor necrosis factor-α (TNF-α) expression and decreased SA-β-gal activity compared to the D1 group. Additionally, co-administration of NAC with 1000 IU of Vit-D significantly downregulated p16 transcripts in PBMCs compared to Vit-D 1000 IU alone. No significant differences were observed between the groups in serum IL-6, C-reactive protein (CRP), or the neutrophil-to-lymphocyte ratio (NLR) after the intervention.ConclusionsThe loading dose of Vit-D significantly attenuates senescence in PBMCs of older adults. However, co-administration of NAC with both the standard and loading doses of Vit-D further enhances these beneficial effects.Clinical trial registrationhttps://irct.behdasht.gov.ir, identifier IRCT20230508058120N1.